Predicting Teachers' Acceptance to Use Computers at Traditional and Innovative Levels in Teaching Mathematics in Serbia - Verica R. Milutinović; Danimir P. Mandić (University of Belgrade, Teacher Education Faculty, 2022)
The aim of this paper is to determine whether pre-service and in-service teachers in Serbia accept to use computers in teaching mathematics and to predict their use of computers at traditional and innovative levels. Research to date has shown that teachers' intention to use computers in their lessons has the greatest impact on their readiness or acceptance to use them. In this research we used the technology acceptance model to examine the predictors of intention, expanded with external variables taken from relevant theories and adapted for mathematics instruction. The following predictors of intention were examined: respondents' attitudes towards computers, their experience with computers in terms of the relative easiness or difficulty of use, their opinions regarding the usefulness of computers, technological-pedagogical familiarity with the content of mathematics, сubjective norm and technological complexity. The analysis of modelling using structural equations, conducted on the sample of 228 in-service and pre-service teachers of mathematics, showed that the proposed model is appropriate and that the given variables are important predictors of teachers' intention to use computers at both traditional and innovative levels in mathematics instruction. On the other hand, the findings indicate that there are differences among in-service and pre-service teachers in terms of the importance of direct and indirect predictors. The technological-pedagogical knowledge of the mathematics content is the dominant predictor of the intention to use computers at all levels, with the exception of the in-service teachers' innovative use of computers. Their intention to use computers in an innovative way is primarily conditioned by their attitudes towards computers. Based on the research results, we offer recommendations for professional development of mathematics teachers, as well as implications for pre-service teachers' education.